Integrating Biophilic Design into Multifunction Space in Shipping Container for Sustainable Living - Sofiana, Yunida; Indahyani, Titi; Aprilia, Hervina Dyah (Talenta Publisher, 2025)
Recently, the intriguing concept of employing shipping containers as residences, stores, or even offices has placed into practice. So it can be concluded that shipping containers can be an alternative space that is functional and be placed in various places (movable). The purpose of this research is to redesign the shipping container as a multifunctional spaces (Staycation-SOHO-Gallery MSME) that can facilitate the needs of urban communities in the endemic era. The application of biophilic design to the interior of the container expected to improve the quality of life and user comfort. The research method used is a descriptive qualitative method with data collection through literature review and field observation, then, data are analyzed using design thinking as part of the design process. The results of this study expected to be part of sustainable living awareness for the community by using shipping containers as a multifunctional space in the public area that can support the welfare and economy of the community during the endemic era. Through the utilisation of these shipping containers, this research aims to propose sustainable living approaches in urban spaces.